Women and Crime - Gulati, Riya (International Journal of Law, Human Rights and Constitutional Studies, 2022)
This paper aims to accentuate the criminal activities that revolves around the women by considering both: Women as offenders and Women as victims . It has been observed that women are less likely to commit criminal offences as compared to men- it is also noteworthy to mention that the women centric laws have been misused and misapplied. Despite of having laws in favour of women, the crime against women are escalating. Henceforth, there is a dire need to remove the loopholes from the system by bringing (necessary) amendments so as to protect the right of an individual and not a particular gender. How to cite this article: Gulati R. Women and Crime. Int Jour Law Hum Rights Const Stud 2020; 2(2): 23-27